Platform Tiktok Sebagai Sarana Ketekese Yang Tepat Bagi Kaum Generasi Z - Skolastika Dinda Ayu Maharani; Emmeria Tarihoran (Jurnal Pendidikan Agama dan Teologi, 2024)
Between 1997 and 2012, this is a generation that is familiar with technology digital and have different preferences in receiving information. The TikTok platform, with its interesting and interactive short video format, has become a popular social media platform among Generation Z. This article aims to explore the potential of the TikTok platform as an appropriate means of catechesis for Generation Z. A literature review was conducted to analyze TikTok's features and characteristics of Generation Z. TikTok features such as short videos, music, and filters can be used to create interesting and interactive catechetical content. Catechesis content on TikTok can be packaged in the form of educational videos, inspirational stories, reflections on faith, and other creative content. The TikTok platform has great potential to become an appropriate catechesis tool for Generation Z. With creative and interactive content, TikTok can help Generation Z to learn about the Catholic faith in an interesting and fun way.